2016
DOI: 10.1387/ijdb.160125bb
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli-based cell-free extract development for protein-based cancer therapeutic production

Abstract: Cell-free protein synthesis has been around for decades but it has never been close to becoming a robust tool for the production of biotherapeutic agents. In this review, we focus on how Escherichia coli-based cell-free protein synthesis can be modified in various ways to produce challenging, complex anticancer biotherapeutics. Here we report progress in extract preparation and its relation to cell-free cancer research. The future prospects of cell-free technology and its potential in various areas of cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…An engineered reporter enzyme domain on the biosensor protein exhibits ligand-dependent activity, resulting in a simple, colorimetric readout. Unique CFPS characteristics, including its chemically accessible reaction environment, robustness, scalability, and control, make this technology a powerful biosensing platform for both simple and complex detection applications. In addition, the ability to lyophilize the CFPS components enables this type of biosensor to be stockpiled for emergencies and biothreat situations.…”
mentioning
confidence: 99%
“…An engineered reporter enzyme domain on the biosensor protein exhibits ligand-dependent activity, resulting in a simple, colorimetric readout. Unique CFPS characteristics, including its chemically accessible reaction environment, robustness, scalability, and control, make this technology a powerful biosensing platform for both simple and complex detection applications. In addition, the ability to lyophilize the CFPS components enables this type of biosensor to be stockpiled for emergencies and biothreat situations.…”
mentioning
confidence: 99%
“…Hence, CFPS (recently also called TXTL for "transcription-translation") is getting more attention these days with the development of new methods that try to make the best use of the unique features of an in vitro method rather than relying on established systems depending on a host cell (Zemella et al, 2015) for synthesis of recombinant proteins. The high potential of new CFPS systems was demonstrated by an E. coli system that is used for protein expression on an industrial scale (Zawada et al, 2011;Salehi et al, 2016;Hershewe et al, 2020). It was suggested that such systems could be used more in the future for the production of dedicated pharma proteins, for example, incorporating noncanonical amino acids (Hong et al, 2014;Quast et al, 2015;Wu et al, 2020), preparation of dedicated proteins that were produced under more defined conditions than possible in cellbased systems (Oza et al, 2015), or allowing for the "on-demand" production of protein therapeutics in the clinic (Mohr et al, 2016;Sullivan et al, 2016;Timm et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutical research and development over the past few decades has discovered treatments for a multitude of diseases including stroke [1], cancer [2] and heart disease [3]. Although these innovative treatments have provided much relief, there is still an economic barrier for many patients in need due to the high cost of drug treatments.…”
Section: Introductionmentioning
confidence: 99%